Blending philosophies: Crafting modern Chinese jewellery aesthetics with a foundation in Eastern wisdom and Western practicality - Boya Yu; Hema Zulaika Hashim (Research Journal in Advanced Humanities, 2024)
Purpose: This study investigates the impact of cultural fusion in contemporary jewellery design on consumer perceptions and purchase intentions. By exploring the prevalence and characteristics of cultural fusion in jewellery design, the study seeks to understand its influence on consumer perceptions of aesthetics, quality, and authenticity. Additionally, the study aims to identify the underlying mechanisms driving consumer responses to culturally fused jewellery designs. Method: A qualitative approach was employed by using semi-structured interviews with 21 experienced Chinese jewellery designers to explore their perspectives on cultural fusion in design. Thematic analysis was performed to identify key themes and patterns in the data. Findings: The study found that cultural fusion plays a significant role in shaping contemporary jewellery aesthetics, with designers drawing inspiration from diverse cultural traditions to create unique and innovative pieces. Consumers responded positively to culturally fused jewellery designs, perceiving them as more aesthetically pleasing, culturally authentic, and desirable compared to traditional designs. Moreover, the study identified several factors driving consumer preferences for culturally fused jewellery, including symbolism, storytelling, and craftsmanship. Implications/Originality: This research contributes to theoretical frameworks on cultural fusion in design and its impact on consumer behavior. By empirically testing the relationships between cultural fusion, design aesthetics, and consumer perceptions, this study advances our understanding of the drivers and outcomes of cultural diversity in the jewellery industry. Moreover, the findings have practical implications for designers, marketers, and policymakers within the jewellery industry, highlighting the importance of cultural fusion in creating culturally resonant and commercially viable jewellery collections.